KECEMASAN IBU DALAM MENGHADAPI PERUBAHAN FISIK MASA MENOPAUSE DI DESA SAMBUNG REJO KECAMATAN SUKODONO KABUPATEN SIDOARJO - WARI, FITRIA EDNI (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2017)
Menopause is the last menstruation of a woman which is often interpreted as the end of functioning reproduction organs. Anxiety often appears, and is attributed to anxiety due to counterpart situations in which women would not want. The feeling of anxiety will risk to a depression. Depression can vary from latiness, less spirit, emptiress, end the feel of meaningless the goal of this research is to know mothers anxiety facing physical changes during menopause in Desa Ngoro Kecamatan Ngoro Kabupaten Mojokerto.This research is a descriptive research. The population is all mothers who have got menopause in Desa Sambung Rejo Kecamatan Sukodono Kabupaten Sidoarjo, as many as 148 people with 60 people as samples , and cluster random sampling as samples taking technique the Variable of this research is mothers anxiety in facing physical changes during menopause. The data were collected by using questionnaires. After data collection data analysis was conducted by using T- Score.The result of the research showed that most respondents suffered  anxiety, as many as 36 respondents (60%) this is caused by the fact that more than a half of the respondents are hausewires, as many as 32 people (53,3%), and almost half of the respondentsonly got  to continue education until junior high school level as many as 10 people (16,7%). Health practitioners are expected to give informations about menopause and be able to give counseling and midwivery training in accordance to mothers need.Keyword : Anxiety, change of physical, menopause